PENERAPAN TEORI CODES AND CONVENTION PADA DESAIN PRODUKSI VIDEO MUSIK GRUNGE MR.HIT - Dedey Rusma Chriszaera Oka Subali; Nyoman Lia Susanthi; Desak Putu Yogi Antari Tirta Yasa (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
Music is a part of culture. But nowadays, some people who listen to music do not know the musicians by the music they hear. Starting in this condition, more effort was needed to introduce musicians. One of the efforts that can be done is through music videos, which is a media for promoting music and musicians. Based on this information, the author wants to promote a grunge music group that is not yet known to many people named Mr.Hit. Mr.Hit was chosen because this music group raised social issues that occurred in society into the song. Based on this phenomenon, writer is interested to create a production design of grunge music video of Mr.Hit. The theory used in this production design consists of codes and convention theory by Goodwin (1992) and logic of visual structure theory by Goodwin (1992). The method in this design is a qualitative method with interpretive analysis. The process of compiling the production design and production techniques as well as the music video theory of "Halusinasi", "Rock Your Way" and "Sang Pejuang" is followed by the design process of production design and production techniques. The result of this creation is the production design and music video production techniques for "Halusinasi", "Rock Your Way" and "Sang Pejuang" as the basis for making music videos which consist of symbols and techniques. In "Halusinasi" writer and the song writer agree on the meaning of the song about a schizophrenic person facing hallucinations and delusions. In the song "Rock Your Way" writer and the song writer agree on the meaning of the song about the spirit of living in any condition. In “Sang Pejuang” writer and the song writer agree on the meaning of the song about the people's struggle to voice their aspirations.